Potassium Deficiency Significantly Affected Plant Growth and Development as Well as microRNA-Mediated Mechanism in Wheat (Triticum aestivum L.) - Zhang, Baohong; Thornburg, Thomas E.; Liu, Jia; Xue, Huiyun; Fontana, Julia E.; Wang, Guo; Li, Qian; Davis, Kyle E.; Zhang, Zhiyong; Liu, Mingjiu; Pan, Xiaoping (Frontiers in Plant Science, 2020)
It is well studied that potassium (K+) deficiency induced aberrant growth and development of plant and altered the expression of protein-coding genes. However, there are not too many systematic investigations on root development affected by K+ deficiency, and there is no report on miRNA expression during K+ deficiency in wheat. In this study, we found that K+ deficiency significantly affected wheat seedling growth and development, evidenced by reduced plant biomass and small plant size. In wheat cultivar AK-58, up-ground shoots were more sensitive to K+ deficiency than roots. K+ deficiency did not significantly affect root vitality but affected root development, including root branching, root area, and root size. K+ deficiency delayed seminal root emergence but enhanced seminal root elongation, total root length, and correspondingly total root surface area. K+ deficiency also affected root and leaf respiration at the early exposure stage, but these effects were not observed at the later stage. One potential mechanism causing K+ deficiency impacts is microRNAs (miRNAs), one important class of small regulatory RNAs. K+ deficiency induced the aberrant expression of miRNAs and their targets, which further affected plant growth, development, and response to abiotic stresses, including K+ deficiency. Thereby, this positive root adaption to K+ deficiency is likely associated with the miRNA-involved regulation of root development.